2001
DOI: 10.1007/s005720100115
|View full text |Cite
|
Sign up to set email alerts
|

Positive growth responses of the medicinal plants Spilanthes calva and Withania somnifera to inoculation by Piriformospora indica in a field trial

Abstract: The medicinal plants Spilanthes calva and Withania somnifera were inoculated with Piriformospora indica, a plant growth-promoting root endophyte, in nurseries and subsequently transferred to the field. A significant increase in growth and yield of both plant species was recorded relative to uninoculated controls. Shoot and root length, biomass, basal stem, leaf area, overall size, number of inflorescences and flowers and seed production were all enhanced in the presence of the fungus. Net primary productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(77 citation statements)
references
References 11 publications
8
68
1
Order By: Relevance
“…Similar results were reported for the medicinal plants, Spilanthes calva and Withania somnifera under nursery and field growth conditions (Rai et al 2001). Greenhouse and field pot culture experiments with P. indica inoculated Hordeum vulgare resulted in significantly increased growth and photosynthesis rates, as well as an enhanced resistance against the specific leave pathogen Blumeria graminis f. sp.…”
Section: Growth Stimulation Of Host Plantssupporting
confidence: 82%
“…Similar results were reported for the medicinal plants, Spilanthes calva and Withania somnifera under nursery and field growth conditions (Rai et al 2001). Greenhouse and field pot culture experiments with P. indica inoculated Hordeum vulgare resulted in significantly increased growth and photosynthesis rates, as well as an enhanced resistance against the specific leave pathogen Blumeria graminis f. sp.…”
Section: Growth Stimulation Of Host Plantssupporting
confidence: 82%
“…For each plant species, 10 roots were selected randomly from the stained roots, and then each selected root was divided into 10 pieces. The percentage of colonization was calculated by the presence of chlamydospores in each piece as follows (Rai et al 2001):…”
Section: Methodsmentioning
confidence: 99%
“…In Baldi's et al (2008) publication, increase of cell growth in suspension cultures of Linum album was dependent on the concentration of fungal cells at co-cultivation cultures. Rai et al (2001) reported that shoot and root length, biomass, basal stem, leaf area, overall size, number of inflorescences and flowers and seed production of Spilanthes calva and Withania somnifera were enhanced in the presence of P. indica in roots. P. indica increased disease resistance and yield of the monocotyledonous plant barley (Waller et al 2005).…”
Section: P S Cmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, mycorrhizal application has shown a substantial increase in the yield properties such as aboveground biomass (Sramek et al, 2000). Although no clear mechanism other than an improvement in the nutritional status has been proposed (Toussaint, 2007), beneficial fungus-plant interactions has shown enhancement in productivity of crops by synthesizing a number of active compounds such as alkaloids, oils, resins, tannins, natural rubber, gums, waxes, dyes, flavors and fragrances, pharmaceuticals, and pesticides (Rai et al, 2001). For example, the suitable selection of host plant-fungus genotype led to an altered accumulation of essential oil levels in arbuscular mycorrhiza-colonized plants of Mentha arvensis (Freitas et al, 2004) and sweet basil Ocimum basilicum L. (Copetta et al, 2006;Copetta et al, 2007;Toussaint, 2007).…”
Section: Utilization Of Beneficial Microorganisms To Increase the Yiementioning
confidence: 99%